Analisis Dampak Industri Batu Bata Terhadap Lingkungan Abiotik di Kelurahan Sengeti Kabupaten Muaro Jambi - M. Irfan Assiddiqi; A.A Miftah; Yuliana Safitri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Industriis a business path that can generate profits and meet needs. One industrithat is very popular at all times is the building raw materials industry, one of which is the brick industry. This research is located in Sengeti Village, Muaro Jambi Regency, where the aim of this research is to determine the impact of the brick industrion the abiotic environment in Sengeti Village, Muaro Jambi Regency. This research uses a descriptive qualitative approach or analysis where data comes from observations, interviews and also direct observations carried out by researchers. Apart from that, researchers also use scientific literature studies as secondary data. The results of this research show that the brick industriitself has quite a large impact on the abiotic environment in Sengeti Village, Muaro Jambi Regency. Among these impacts are the large number of excavated holes, decreased quantity and quality of soil, decreased water quality, air pollution, damage to road access. The solutions that researchers offer are, processing former excavated holes into fish ponds, arranging excavation sites, processing waste, using chimneys with pollutant filters, and making roads using cement concrete.